2024
DOI: 10.1039/d3su00309d
|View full text |Cite
|
Sign up to set email alerts
|

Evolving sustainable energy technologies and assessments through global research networks: advancing the role of blue hydrogen for a cleaner future

Israel Oliveira Cavalcante,
Francisco Simão Neto,
Patrick da Silva Sousa
et al.

Abstract: Considering the interest in innovations in the energy sector and government policies that seek an energy system free of polluting agents, blue hydrogen, whose production takes place through fossil fuels...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…This study builds on previous research [28,[50][51][52][53][54][55][56][57][58][59] and uses bibliometric analyses with data from the Web of Science (WoS) (https://www.webofscience.com (accessed on 27 December 2023)), a reliable platform for scientific publications that is widely recognized for its high quality and accepted standards in generating research citation data [60,61].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study builds on previous research [28,[50][51][52][53][54][55][56][57][58][59] and uses bibliometric analyses with data from the Web of Science (WoS) (https://www.webofscience.com (accessed on 27 December 2023)), a reliable platform for scientific publications that is widely recognized for its high quality and accepted standards in generating research citation data [60,61].…”
Section: Methodsmentioning
confidence: 99%
“…Collaboration between institutions can significantly impact the progress of research in the area of fermentation for hydrogen production, as shown by the bibliometric analysis that highlights, among other aspects, collaboration agreements between different institutions and significant partnerships [28,52,54,58]. These collaborative networks are valuable for accumulating knowledge and resources, bringing a diversity of approaches to the field, where different institutions can contribute with specific focuses, from microbiology to energy policies, enriching research by addressing hydrogen production from various perspectives [214][215][216][217].…”
Section: Overviewmentioning
confidence: 99%
“…Bibliometrics focuses on metadata analysis of relevant published publications, which uses statistical data to describe and analyze the connections between published information . Along with bibliometrics being widely researched in various forms, bibliometric mapping software tools have been rapidly developed . The visualization tools used in the paper include VOSviewer, CiteSpace, and HistCite.…”
Section: Methodsmentioning
confidence: 99%